The Effect Of Inflation, Exchange Rate, Bi Rate And Sbm Commodity Prices Moderated By Profitability On The Value Of Companies In The Animal Feed Sub-Sector Industry On The Indonesia Stock Exchange In 2017-2022 - Noviadi Suryawan; Sunita Dasman; Preatmi Nurastuti (Dinasti Publisher, 2024)
This study investigates the effect of inflation, exchange rate, BI rate, and SBM commodity prices moderated by profitability on the value of companies in the animal feed sub-sector industry listed on the Indonesia Stock Exchange from 2017 to 2022. Using quantitative methods and Eviews for data analysis, the study tests eight hypotheses to determine the relationships and moderating effects. The results show no significant effect of inflation on PBV, a significant negative effect of exchange rate on PBV, a significant positive effect of the BI rate on PBV, and a significant positive effect of SBM commodity prices on PBV. Moreover, the interaction between inflation and profitability shows a significant negative effect on PBV, while the interactions between exchange rate and profitability, and SBM commodity prices and profitability, show no significant effects. The interaction between BI rate and profitability shows a significant positive effect on PBV. These findings provide insights into the dynamics of macroeconomic variables and company value in the animal feed sub-sector, suggesting avenues for further research and implications for policy and investment strategies.